Structurally Characterized Cobalt and Nickel Complexes of Flavonoid Chrysin as Potential Radical Scavenging Compounds - Eleftherios Halevas; Barbara Mavroidi; Despoina Varna; Georgia Zahariou; George Litsardakis; Maria Pelecanou; Antonios G. Hatzidimitriou (Inorganics, 2025)
Polyphenolic compounds, such as flavonoids, possess important structural and physico-chemical characteristics that in combination with their biological properties render them an important class of natural compounds with medicinal prospects. Chrysin is a well-known flavone with antioxidant activity and a multitude of other beneficial properties. The potential of flavonoids to coordinate with metal ions leads to derivatives with enhanced biological profile. Within this framework, four novel heteroleptic complexes of cobalt and nickel with chrysin and the aromatic bidentate chelating agents 2,2′-bipyridine and 1,10-phenanthroline were synthesized, as well as physico-chemically and structurally characterized. The in vitro antioxidant efficiency of the synthesized complexes was examined via the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. All complexes showed notable radical scavenging capacity comparable to that of ascorbic acid, providing the incentive for further investigation of their therapeutic potential.